UNIVERSAL JURISDICTION FOR TERRORISM CRIMES: A STUDY OF TERRORISM AS CRIMES AGAINST HUMANITY - Yustitianingtyas, Levina; Pratiwi, L.Ya Esty; Sulistyo, Al Purwo Qodar; Irawan, Anang Dony (TANJUNGPURA LAW JOURNAL, 2026)
Abstract Categorizing terrorism as an international crime is not wrong, because the international elements of the crime have been fulfilled. Terrorist crimes involve more than one state, each possessing its own legal system and jurisdictional framework. A number of terrorist acts have been recorded as having disrupted international security stability, including those carried out by networks such as Al-Qaeda, ISIS, and others. In addition to these global terrorist groups, there are also well-known terrorist groups in the Southeast Asian region, namely the Abu Sayyaf Group. This legal research aims to examine universal jurisdiction over terrorism as an international crime, on the basis that terrorist acts may be considered to satisfy the elements of crimes against humanity, insofar as such acts are intentionally committed as part of a widespread attack, involve multiple actors, and target civilian populations at large. This research employs a qualitative normative legal method, utilizing a statute approach and a case approach, and drawing upon primary, secondary, and tertiary legal materials. The findings indicate that the formulation of crimes against humanity constitutes the most appropriate legal basis for prosecuting terrorism under the jurisdiction of the International Criminal Court (ICC). The absence of a universally accepted definition of terrorism has resulted in terrorism not yet being included within the jurisdiction of the ICC. Furthermore, the failure at the regional level to effectively resolve issues related to terrorism underscores the need for a universally agreed definition of terrorism so that perpetrators may be prosecuted before international courts. Strengthened cooperation among states, both at the regional and global levels, is therefore necessary to ensure the effective eradication of terrorist crimes. Abstrak Mengkategorikan terorisme sebagai kejahatan internasional tidaklah salah, karena unsur-unsur internasional dari kejahatan tersebut telah terpenuhi. Dimana kejahatan terorisme melibatkan lebih dari satu negara yang di dalamnya terdapat sistem hukum dan penerapan yurisdiksi. Beberapa tindakan terorisme telah tercatat mengganggu stabilitas keamanan internasional, termasuk jaringan Al-Qaeda, ISIS dan sebagainya. Selain kelompok teroris di dunia, terdapat pula kelompok teroris yang cukup terkenal di kawasan Asia Tenggara, yaitu Kelompok Abu Sayyaf. Penelitian hukum ini bertujuan untuk mengkaji yurisdiksi universal terorisme sebagai kejahatan internasional, karena kejahatan terorisme dapat dikatakan memenuhi unsur-unsur kejahatan terhadap kemanusiaan, yang mana tindakan dilakukan dengan sengaja sebagai bagian dari serangan yang meluas, melibatkan banyak pihak dan menargetkan semua warga negara. Penelitian hukum ini menggunakan metode normatif kualitatif, dengan statute approach dan case approach, serta bahan hukum yang digunakan yaitu bahan hukum primer, sekunder dan tersier. Hasil dari penelitian ini menunjukkan bahwa pelanggaran kejahatan terhadap kemanusiaan dianggap sebagai formulasi yang paling tepat untuk mengadili kejahatan terorisme di bawah yurisdiksi ICC. Ketiadaan definisi terorisme yang universal menyebabkan hingga saat ini terorisme belum masuk dalam yurisdiksi ICC. Kegagalan di level regional untuk menyelesaikan permasalahan terorisme sehingga diperlukan kesepakatan definisi terorisme secara universal sehingga para pelaku kejahatan tersebut dapat di adili dalam peradilan internasional. Perlunya penguatan kerjasama antar negara baik di level regional maupun global agar pemberantasan kejahatan terorisme dapat maksimal.